2019
DOI: 10.3389/fnagi.2019.00087
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Cerebrospinal Fluid Flow Is Associated With Cognitive Deficit in Elderly Patients

Abstract: Background: Disruptions in cerebrospinal fluid (CSF) flow during aging could compromise protein clearance from the brain and contribute to the etiology of Alzheimer’s Disease (AD). Objective: To determine whether CSF flow is associated with cognitive deficit in elderly patients (>70 years). Methods: We studied 92 patients admitted to our geriatric unit for non-acute reasons using phase-contrast magnetic resonance imaging (PC-MRI) to calculate their ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 63 publications
(81 reference statements)
1
34
1
1
Order By: Relevance
“…Concomitant conditions such as age, diabetes and chronic renal failure or left ventricle systolic function occurred independent determinants of cognitive status. This is in line with data from observational studies [35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Concomitant conditions such as age, diabetes and chronic renal failure or left ventricle systolic function occurred independent determinants of cognitive status. This is in line with data from observational studies [35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 91%
“…Diabetes occurred an important predictor of cognitive decline in the elderly, associated with deficits in attention and executive functions in some studies, whereas the greater the severity of chronic kidney disease, the greater the progression of cognitive decline was observed [35][36][37][38]. At present, the main treatment for vascular cognitive impairment is prevention by treating vascular diseases and other risk factors, such as hypertension and diabetes mellitus [40].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, age and sex only explain a small part of the variability of values of CSF flow dynamics parameters in the aqueduct as demonstrated by the adjusted R 2 of the linear regression models. Yet this is not surprising as CSF flow in the aqueduct may be impacted by various factors such as biochemical parameters or cerebrovascular and brain pulsation (Mase et al, 1998; Chiang et al, 2009; Schmid Daners et al, 2012; Puy et al, 2016; Attier-Zmudka et al, 2019). Nonetheless between 6 and 18% of the variability in all parameters may be explained only by the two factors sex and age.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a very recent study (Attier-Zmudka et al, 2019) has observed decreased CSF flow in elderly patients with cognitive deficits whereby ventricular CSF flow was significantly associated with patient’s performance on an instrumental cognition test.…”
Section: Discussionmentioning
confidence: 99%
“…CSF turnover can also be disrupted during aging. One recent study demonstrated significantly reduced CSF flow during aging by calculating ventricular and spinal CSF flow in a cohort of elderly participants (Attier-Zmudka et al, 2019 ) which was associated with cognitive performance. Since CSF is important for transporting ascorbate into the extracellular neuronal space and is the fluid which neurons are exposed to, possibly the impaired CSF flow during aging could be associated with reduced transportation of ascorbic acid into neurons.…”
Section: Age Modulationmentioning
confidence: 99%